Development of a Clinical Risk Assessment Tool for 6-Week Postpartum Visit Nonadherence - Qafiti, Fred; Kaur, Sangeeta; Bahado-Singh, Ray (American Journal of Perinatology, 2018)
Objective The 6-week postpartum visit (6WPP) is integral in addressing postpartum medical concerns. Failure to attend this routine visit is a measure of suboptimal care. This study aims to identify patients at risk of 6WPP nonadherence by developing a novel point-based risk scoring system.Methods In this retrospective case–control study (n = 587), a randomly selected subgroup, that is, the “test” group (n = 303), was used to develop the model. The remaining patients were used as an independent “validation” group (n = 284) to assess the model performance.Results Five factors were found to correlate with 6WPP nonadherence. Positive correlations include: Medicaid health insurance (odds ratio [OR]: 2.40, 95% confidence interval [CI]: 1.38–4.15); prenatal care initiated at ≥ 14 weeks' gestation (OR: 1.82, 95% CI: 1.11–2.96); and maternal age < 24.0 years (OR: 2.02, 95% CI: 1.13–3.61). Factors negatively correlated with nonadherence include: “married” marital status (OR: 0.50, 95% CI: 0.30–0.84) and primiparity (OR: 0.51, 95% CI: 0.30–0.85). The final scoring system demonstrates significant predictive power in both the test and validation groups (respectively, area under the curve = 0.682, p < 0.001 and 0.629, p < 0.001).Conclusion This risk assessment tool relies on routinely collected data, making its implementation simple. Applying it in the clinical setting allows for early, targeted intervention aimed at minimizing 6WPP nonadherence.
Keywords: postpartum visit; risk factors; nonadherence; risk assessment; predictive modeling